IMAGINATION, MEMORY, AND ATTENTION DEVELOPMENT IN CHILDREN WITH AUTISM - Kahramonova Zebuniso Raufjonovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation.This article analyzes the characteristics of imagination, attention, and memory in children with autism. The peculiarity of attention is that involuntary attention may manifest with high intensity, but its prolonged duration can lead to emotional distress and affective outbursts. The formation of voluntary attention occurs with significant difficulty. In the memory process, children with preserved intelligence may have well-developed involuntary auditory and visual memory, especially in remembering logical symbols and formulas effectively. Logical voluntary memorization, however, depends on the child's interests and level of motivation.